Deficiency of rice hexokinase HXK5 impairs synthesis and utilization of starch in pollen grains and causes male sterility. (31st October 2019) - Lee, Sang-Kyu; Kim, Hyunbi; Cho, Jung-Il; Nguyen, Cong Danh; Moon, Sunok; Park, Jeong Eun; Park, Hye Rang; Huh, Jin Hoe; Jung, Ki-Hong; Guiderdoni, Emmanuel; Jeon, Jong-Seong
Abstract : Analysis of rice hexokinase hxk5 mutants reveals that the function of OsHXK5 in starch biosynthesis and utilization is essential for normal pollen development, germination, and tube growth. Abstract: There is little known about the function of rice hexokinases ( HXK s) in planta . We characterized hxk5-1, a Tos17 mutant of OsHXK5 that is up-regulated in maturing pollen, a stage when starch accumulates. Progeny analysis of self-pollinated heterozygotes of hxk5-1 and reciprocal crosses between the wild-type and heterozygotes revealed that loss of HXK5 causes male sterility. Homozygous hxk5-1, produced via anther culture, and additional homozygous hxk5-2, hxk5-3 and hxk5-4 lines created by CRISPR/Cas9 confirmed the male-sterile phenotype. In vitro pollen germination ability and in vivo pollen tube growth rate were significantly reduced in the hxk5 mutant pollen. Biochemical analysis of anthers with the mutant pollen revealed significantly reduced hexokinase activity and starch content, although they were sufficient to produce some viable seed. However, the mutant pollen was unable to compete successfully against wild-type pollen. Expression of the catalytically inactive OsHXK5-G113D did not rescue the hxk5 male-sterile phenotype, indicating that its catalytic function was responsible for pollen fertility, rather than its role in sugar sensing and signaling. Our results demonstrate that OsHXK5 contributes to a large portion of the hexokinase activity necessary for the starch utilization pathway during pollen germination and tube growth, as well as for starch biosynthesis during pollen maturation.